WASIAT WAJIBAH BAGI ANAK ANGKAT DALAM HARTA WARIS MELALUI PUTUSAN NOTARIS - Muhammad Zainuddin Sunarto; Viqi Fadilatur Rizqiyah (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2021)
In the context of inheritance law, children are a separate discussion, because the presence of a child makes a very exciting thing for every couple. It is easy for those who are biological children, because it will not cause a problem if he gets a share of the inheritance of his parents because he is one of the legal heirs. However, the context is different if this happens to an adopted child who does not actually get a share in the inheritance law. so that researchers feel the need to do a research related to the inheritance of adopted children, how to divide inheritance, a forum for adopted children to get inheritance, and legal force which is evidence that adopted children are entitled to inherit property By using the library research method, the researcher found that the adopted child could inherit the inheritance from his adoptive parents through the mandatory will process with the provision that it should not be more than 1/3 of the inheritance of his adoptive parents before it was distributed to other heirs. With this decision, it is necessary to have an authentic deed from the notary as strong evidence for the adopted child if in the future there is a dispute regarding the assets he has received. The decision from a notary in the form of an authentic deed is evidence that has the highest legal force in overcoming disputes related to the distribution of inheritance.